Pyramid shape power as a new halal-compliant food preservation and packaging technique - Abdelsamie, Maher Abdelaleem Abdelrazik; Abdul Rahman, Russly; Mustafa, Shuhaimi (2012)
Halal food production is an integrated process from farm to fork, to produce not only food that is ritually blessed but must be healthy, safe, and innocuous which means (Tayyib). As the reduction of some nutrients, vitamins, and quality caused by most current preservation techniques, a search for safer alternative technique is a top priority research in the area of food science. The new technique combines preservation and packaging in one process, This technique based on the mystery of the dimensional ratio of the Great Pyramid of Giza in Egypt and its effect on the growth of microorganisms when applied on pyramidal food packages and containers, the shape power is the only responsible factor for the preservation effect without any other physical or chemical treatment. This paper also presents the preservation efficacy of the method that will be assessed by various parameters such as pH, odour, colour and bacterial count.